Factor Affecting Mobile Adoption Companies in Malaysia - Mahad, Murat; Mohtar, Shahimi; Yusoff, Rushami Zein; Othman, Abdul Aziz (International Journal of Economics and Financial Issues, 2015)
Mobile banking refers to the use of smart phones or other mobile devices to perform tasks online banking from your home computer, such as monitoring the account balances, transfer of funds between accounts, pay bills and prepaid top-up. Mobile banking is a new strategy for the bank to enhance their latest technology in a new dynamic marketing environment. The low penetration of mobile banking in Malaysia, especially in terms of adoption patterns is becoming the research interest, especially when compared to the total number of cellular telephone subscriptions, which recorded the highest number of penetration rates in quarter three of 146.2 percent in 2013. Although the number of cellular telephone users is huge, yet the mobile banking penetration rate was just 12.7 percent last year against the total population. This implies that those who employ the mobile banking market is still the minority. Thus, more effort needs to be practiced to amend the number of users and penetration rate of mobile banking. Even if mobile banking is relatively new in Malaysia, it is very important for the banks to mitigate this issue and thus can draw more users. It is a fact that mobile banking is yet in its infancy and quite foreign to the people of Malaysia. The purpose of this study was to explore the affecting factors of intention to use of mobile banking in Malaysia. The issue of risk in term of security, privacy, financial, time and performance are the five important dimensions in risk factor that may affect the user’s intention to adopt the mobile banking services. Therefore, this study attempts to further discuss on the elements of risk to have a better understanding of the adoption of the mobile banking. The findings of this study are very important for the banking services in Malaysia to have a better outcome and strategy to increase the penetration rate of mobile banking users. Keywords: Mobile Banking; Decomposed Theory of Planned Behavior; Perceived Risk JEL Classifications: M00